Impact of Auditory Deprivation on Tennis Performance and Perceived Exertion - Kolar, Jachym; Kolar, Pavel; Modrak, Martin; Veselý, Viktor; Kobesova, Alena (International journal of sports physiology and performance, 2025)
PURPOSE: This study aimed to evaluate the impact of auditory deprivation on tennis-stroke accuracy and perceived exertion among tennis players, with a focus on understanding how auditory inputs affect sport performance. METHODS: A total of 77 active tennis players participated in this controlled trial, which involved playing tennis under standard auditory conditions and with auditory deprivation using noise-isolation devices. Data were collected using a Zepp Tennis Smart Sensor 2 to assess hit accuracy, and the Borg Rating-of-Perceived-Exertion (RPE) scale was used to measure exertion levels. RESULTS: Players demonstrated significantly lower accuracy in hitting the center of the racket under auditory deprivation compared with standard auditory conditions (OR: 0.71, 95% CI, 0.68 to 0.75, P < .001). Additionally, auditory deprivation resulted in higher reported exertion levels, with 75% of participants reporting increased RPE compared with standard conditions (95% CI, 64% to 84%, P < .001). CONCLUSIONS: Auditory deprivation negatively impacts both the accuracy of tennis strokes and the subjective experience of exertion in players. These findings highlight the importance of auditory cues in sport performance and suggest that integrating sensory feedback can enhance athletic training and performance strategies. This study supports further exploration of sensory inputs' role in sport and their potential in training regimens.
Keywords: performance metrics; dospělí; Humans; exercise tolerance; tělesná námaha; Physical Exertion; Athletic Performance; Perception; sportovní výkon; mladý dospělý; percepce; Feedback, Sensory; mužské pohlaví; noise isolation; Adult; senzorická zpětná vazba; senzorická deprivace; sensory feedback; ženské pohlaví; Sensory Deprivation; lidé; podněty; Tennis; tenis; Male; Young Adult; Cues; motor skills; Female